1971
DOI: 10.1159/000220713
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Evaluation of the Effect of Actinomycin D, Daunomycin, and Mitomycin C on Proliferating Cultured Leukemia L1210 Cells

Abstract: Proliferating cultured leukemia L1210 cells exposed to cytotoxic concentrations of actinomycin D, daunomycin, or mitomycin C are killed at a rate which is relatively dependent upon the concentrations used. On an equimolar basis, proliferating L1210 cells are equally sensitive to actinomycin D or daunomycin and are the least sensitive to mitomycin C. Nonproliferating L1210 cells are sensitive to these agents in vitro. The nonproliferating cells are the most sensitive to actinomycin D, less sensitive to daunomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Actually, the large amount of the normal CFU killed by the drug outside the S-phase cannot be accounted for without including the Go population. This observation was at variance with the difference in the toxic effects found between proliferative and non-proliferative mammalian tumour cells (Wilkoff et al, 1971), although their non-proliferating populations are stopped from growth (Schabel et al, 1965) in contrast to normal bone marrow CFU whose proliferation is balanced by death and differentiation. Cell culture studies have shown that GI (and G2) cells are sensitive to Mitomycin-C (Djordjevic & Kim, 1968).…”
Section: Toxicity Of Mitomycin-c Against Cells In Dijferent Phases Ofmentioning
confidence: 97%
See 1 more Smart Citation
“…Actually, the large amount of the normal CFU killed by the drug outside the S-phase cannot be accounted for without including the Go population. This observation was at variance with the difference in the toxic effects found between proliferative and non-proliferative mammalian tumour cells (Wilkoff et al, 1971), although their non-proliferating populations are stopped from growth (Schabel et al, 1965) in contrast to normal bone marrow CFU whose proliferation is balanced by death and differentiation. Cell culture studies have shown that GI (and G2) cells are sensitive to Mitomycin-C (Djordjevic & Kim, 1968).…”
Section: Toxicity Of Mitomycin-c Against Cells In Dijferent Phases Ofmentioning
confidence: 97%
“…In HeLa cell cultures, the drug has been found to be more toxic to cells other than those in the S-phase (Djordjevic & Kim, 1968). Some workers (Doi et al, 1967) have reported that the latter half of the GI-phase and first half of the S-period are highly sensitive to Mitomycin-C. Non-proliferative L1210 cells have been found to be much less sensitive to the agent than proliferative cells (Wilkoff, Lloyd & Dulmadge, 1971).…”
mentioning
confidence: 99%